IDENTIFIKASI PENYAKIT VASCULAR STREAK DIEBACK (VSD) DAN TINGKAT SERANGAN SERTA PENGARUHNYA PADA PERTUMBUHAN KAKAO DI TIGA DESA KEC. PALOLO KAB. SIGI - Syarif, Mohammad (JSTT, 2016)
The aim of this study is to identify VSD attacks to cocoa crop in three villages in Palolo. b.analize the way of VSD infecting cocoa crop in three villages, in Palolo, Sigi. c.how to cut the attack and control the damage caused by VSD to cocoa in three villages in Palolo. This study using identification method. The research method that is conducted through observation of the leaves, twigs and branches of the cocoa plant which suspect attacked by VSD in the field and observation in laboratory to ensure that the attack VSD on cocoa in the three villages in Palolo actually happened , as well as focusing on actual problems of the development of VSD. The research was conducted in three villages names Ampera, berdikari and Rejeki village in Palolo. Determination of the location of the research done on purpose (purposive method), with the consideration that all three of the village is the center of development of cocoa production in Palolo. This research was conducted for three months from January to April 2015 and then continued by observing VSD in the laboratory of pest and disease Agriculture faculty, Tadulako University. VSD has been informed attacking almost all the province which producing cocoa in Indonesia. In 2000, there were VSD attacks reaches 6000 ha with yield losses Rp 405 643 680 000 / year. The number of the attack until May 2001 reached 70 000 ha with a loss of billions rupiah (Ditjenbun, 2007). The observation result like contained in Tabel 1 show that in average the intensity attacks of VSD from the research site showed that cocoa in Berdikari has the highest VSD attack it is 16.9%, on the contrary VSD attack in Ampera and Rejeki are low attack each of them 12 , 5% and 12.1%. This shows that in all three villages have been found the attack of VSD as seen in the field, where the characteristic of attack ,the leaves infected of VSD changes the color to yellow with green patches on the surface of the leaves, and the leaves will eventually fall. In the former leaves holder which is affected by VSD will appear visible three point brown indicates that the plant has been attacked by VSD, meanwhile on the twig attacked, if observed in detail and touched with fingers, it would seem that the surface of twig is uneven because it has been Swelling occurs on the surface, so that within a certain time the branch would dry up and will seem toothless, this happens because the VSD disease has progressed on the xylem and hinder the process of transformation of food to other plant tissues. These events will cause significant changes in plants, from healthy plants become dry due to the intake of food that goes into the xylem become obstructed. With the special mark left by VSD on branches and twigs of cocoa plants in three villages can be assumed that in Palolo, there has been a VSD attacks caused by fungi Oncobasidium theobromae (Basidiomycetes).